Efficacy of Hyaluronic Acid in Patients with Osteoarthritis of The Knee - Ali Hasanain Alhamadani (Indian Journal of Forensic Medicine & Toxicology, 2021)
Osteoarthritis (OA) of the knee is the most common chronic degenerative joint disease characterized by pain,stiffness, swelling and progressive functional limitation in elderly. Non-surgical management modalitieslike physical therapy, lifestyle modification and oral non-steroidal anti-inflammatory drugs, are oftenineffective or do not alleviate symptoms adequately. Intra-articular corticosteroid (CS) and hyaluronic acid(HA) injections have been used for long to alleviate the symptoms of knee OA. viscosupplementation hasbeen used as a therapeutic modality for the management of knee OA. The principle of viscosupplementationis based on the physiological properties of the hyaluronic acid (HA) in the synovial joint which helps tissuelubricate, cushion and reduce pain in the joint.Study diagnosed forty patient of knee Osteoarthritis for both gender with age (45-70 years) and observedchange and effectiveness to pre-and post of HA injection, All patients diagnosed by Orthopedists andRheumatologists whose used X-rays were graded as stage I, II and III according to Kellgren and Lawrencescale.All the measurements were used at the time of enrollment in the study before any injection and then measuredagain at the end of three months by using Western Ontario and McMaster University Osteoarthritis Index(WOMAC) .All the patients before therapy were having minimum score of 72.4 & 9.045 for Mean and Standard Deviationrespectively while after the therapy there score reduced to 36.2 & 4.783.The results show improvement significant during four month under study and the effect peaks at around8–12 weeks following administration, This supports the potential use of intra-articular HA as an effectivelong therapeutic option for patients with OA of the knee.